Registros da fé: ex-votos fotográficos e a relação entre receber e devolver na sala dos milagres em Trindade, GO - Santos, Phelipe Augusto Silva (2024)
The present study aims to analyze the dynamics of photographic ex-votos in the Miracle Room at Trindade, Goiás, highlighting the relationship between receiving and giving back within this religious context. The cultural and identity importance of the pilgrimage to the Divine Eternal Father is also explored. In this scope, our objective was to investigate how photographic ex-votos are used as expressions of faith and gratitude in the Miracle Room, as well as to analyze the identity construction of the faithful through these religious practices. The research methods used included participant observation, documentary analysis, and access to photographs left by devotees, with the investigation previously approved by the PUC GOIÁS Ethics Committee, under number CAAE: 75726123.1.0000.0037. In summary of the obtained results, we highlight the significance of photographic ex-votos as a means of communication between the human and the divine, and how they contribute to strengthening community bonds and religious identity. Finally, we present some conclusions, emphasizing the relevance of photographic ex-votos in the religious experience of the faithful, as well as their role in constructing meanings and devotion practices. Additionally, we highlight some contributions in the field of Religious Studies and Visual Culture. The research was partially funded by the Coordination for the Improvement of Higher Education Personnel (CAPES) through a scholarship grant